ДИВЕРСИФІКАЦІЯ МОДЕЛЕЙ ПОСЕРЕДНИЦТВА НА ГЛОБАЛЬНОМУ РИНКУ ПРОДОВОЛЬСТВА (International Journal of Innovative Technologies in Economy, 2018)
The article researches intermediation models on the global food market using explicative method. The author proposes to diversify intermediation models on the basis of provided classification by thirteen criteria. The article proposes to divide intermediaries according to the activity field into trade, production, logistics, marketing, financial, legal, informational, administrative, and technical intermediaries. Each type has its description in the article. Particular attention is drawn to trade and marketing intermediaries. Moreover, the article groups intermediaries by the following characteristics: on behalf of whom an intermediary works; on whose account an intermediary works; type of influence on product; activity type; territory; exclusiveness; systematicness; market sector. The article provides lists of the most important intermediation models that correspond to the groups. The models can be diversified by one or several of the proposed criteria. Moreover, some models can be indifferent to a definite characteristic or appear in different groups simultaneously.